Thyroid dysfunction and semen quality among males investigated for infertility in Southern Nigeria - Mathias Abiodun Emokpae; Irabonosa Asiriuwa; James Agbonmwanre Osaikhuwuomwan (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2024)
The relationship between thyroid and testis is well understood, and the association between changes in thyroid function and male infertility has been reported. However, the contribution of thyroid dysfunction to male infertility is not sufficiently addressed in our setting. This study aims to assess the thyroid hormones level among males undergoing investigation for infertility and to establish correlations between thyroid hormones and sperm indices. Thyroid hormones were determined in 150 infertile males and 50 fertile male controls. Semen analysis was done according to the World Health Organization criteria while thyroid hormones were determined using Enzyme linked Immunosorbent assay technique. The measured anthropometric data, sperm indices and thyroid hormone levels were compared using appropriate statistical tools. Serum triiodothyronine, and thyroxine levels were significantly lower (p < 0.001), while thyroid stimulating hormone was higher among infertile males than control subjects. The body mass index of the infertile subjects was significantly higher (p < 0.011) than control subjects. Of the 150 subjects, 41.33% (62/150) were euthyroid, 7.33% (11/150) had subclinical hypothyroidism while 51.34% (77/150) had overt hypothyroidism. Among the 88 altered thyroid function, 6.82% (6/88) had normozoospermia, 44.32% (39/88) had oligozoospermia while 48.86% (43/88) were azoospermia. The area Under the Curve of T3 (0.858), T4 (0.765) and sperm count (0.875) were able to differentiate fertile men from infertile subjects. Thyroid disorders are prevalent among infertile men and should be considered in the laboratory assessment of male infertility cases. Including thyroid function tests in the investigative panel can help identify and manage potential thyroid-related factors contributing to infertility. This comprehensive approach ensures thorough evaluation and targeted treatment for better reproductive outcomes in affected individuals.